A Nice Radical Equation With Parameters

Поделиться
HTML-код
  • Опубликовано: 4 фев 2025
  • 🤩 Hello everyone, I'm very excited to bring you a new channel (SyberMath Shorts).
    Enjoy...and thank you for your support!!! 🧡🥰🎉🥳🧡
    / @sybermath
    / @aplusbi
    ⭐ Join this channel to get access to perks:→ bit.ly/3cBgfR1
    My merch → teespring.com/...
    Follow me → / sybermath
    Subscribe → www.youtube.co...
    ⭐ Suggest → forms.gle/A5bG...
    If you need to post a picture of your solution or idea:
    in...
    #algebra #counting #geometry #numbertheory #calculus
    via @RUclips @Apple @Desmos @NotabilityApp @googledocs @canva
    PLAYLISTS 🎵 :
    ▶ Trigonometry: • Trigonometry
    ▶ Algebra: • Algebra
    ▶ Complex Numbers: • Complex Numbers
    ▶ Calculus: • Calculus
    ▶ Geometry: • Geometry
    ▶ Sequences And Series: • Sequences And Series

Комментарии • 15

  • @mikeyu3243
    @mikeyu3243 3 месяца назад +4

    Inversed: 1/(sqrt(x+a)+sqrt(x)) = 1/a
    multiply sqrt(x+a)-sqrt(x) to left, the result is 1

  • @icfj77
    @icfj77 3 месяца назад +2

    this problen has sense only for a=0, and a>1, a=1.

  • @chaosredefined3834
    @chaosredefined3834 3 месяца назад +1

    Method 4. In other words, how I'd do it if I didn't spot the diff of squares.
    sqrt(x + a) + sqrt(x) = a
    sqrt(x + a) - sqrt(x) = b
    Subtract the two:
    2 sqrt(x) = a - b
    Divide through by 2
    sqrt(x) = (a - b)/2
    Square it
    x = (a^2 - 2ab + b^2)/4
    Add the initial two:
    2 sqrt(x + a) = a + b
    Divide through by 2
    sqrt(x + a) = (a + b)/2
    Square it
    x + a = (a^2 + 2ab + b^2)/4
    Substituting in the x from the subtraction step:
    (a^2 - 2ab + b^2)/4 + a = (a^2 + 2ab + b^2)/4
    Multiplying through by 4
    a^2 - 2ab + b^2 + 4a = a^2 + 2ab + b^2
    Subtract a^2 + b^2 from both sides
    -2ab + 4a = 2ab
    Add 2ab to both sides
    4a = 4ab
    Either a = 0 or b = 1.
    Well, we wanted b. So, b = 1, unless a = 0. Let's check that cases:
    sqrt(x + 0) + sqrt(0) = 0
    sqrt(x) = 0
    x = 0
    sqrt(0 + 0) - sqrt(0) = 0 - 0 = 0.
    So, if a = 0, then b = 0. Otherwise, b = 1.

  • @ProactiveYellow
    @ProactiveYellow 3 месяца назад

    Given the first equation, we have
    √(x+a)+√x=a
    Add and subtract x on the right
    √(x+a)+√x=x+a-x
    We can factor a difference of squares on the right
    √(x+a)+√x=(√(x+a)+√x)(√(x+a)-√x)
    Notice that the LHS and RHS have the same expression multiplied by our target expression. This only works in two cases:
    1. The LHS expression is 0. If this is the case, then √(x+a)+√x=0=a →2√x=0→x=0, so √(x+a)-√x=√(0+0)-√0=0
    2. The target expression is the multiplicative identity, that is, √(x+a)-√x=1
    These are the only two solutions.

  • @surenderkumar4560
    @surenderkumar4560 3 месяца назад

    Rationalize the numerator and the answer in the 2nd step is 1

  • @paulortega5317
    @paulortega5317 3 месяца назад

    Method 3 please. LOL

  • @yakupbuyankara5903
    @yakupbuyankara5903 3 месяца назад

    1

  • @Kraken-lm1cx
    @Kraken-lm1cx 3 месяца назад

    I just multiplied sqrt(x + a) + sqrt(x) = a by sqrt(x + a) - sqrt(x) on both sides to get:
    a = a(sqrt(x + a) - sqrt(x) )
    Clearly if a != 0, sqrt(x + a) - sqrt(x) = 1

  • @Uranyus36
    @Uranyus36 3 месяца назад

    simple:
    for a =/= 0,
    (sqrt(x+a) + sqrt(x))(sqrt(x+a) - sqrt(x)) = x + a - x
    a(sqrt(x+a) - sqrt(x)) = a
    (sqrt(x+a) - sqrt(x)) = 1
    for a = 0, x = 0 so (sqrt(x+a) - sqrt(x)) = 0

  • @jacobcohen2957
    @jacobcohen2957 3 месяца назад

    The solution is valid for a>1.
    Otherwise, sqrt(x) = (a-1)/2 is negative.

  • @maxgoldman8903
    @maxgoldman8903 3 месяца назад

    Do we need to consider the absolute value for √ (·)² appearing in method 1 and 2 when there’s no specification on parameter a?

    • @omni-e1w
      @omni-e1w 3 месяца назад

      Absolutely.

  • @yurenchu
    @yurenchu 3 месяца назад

    Answer:
    √(x+a) - √x = 1 OR √(x+a) - √x = 0
    Calculation:
    √(x+a) + √x = a
    √(x+a) - √x = ?
    (√(x+a) + √x) * (√(x+a) - √x) =
    = (√(x+a))² - (√x)²
    = (x+a) - x
    = a
    ==>
    (√(x+a) + √x) * (√(x+a) - √x) = a
    and
    (√(x+a) + √x) = a
    ==>
    a * (√(x+a) - √x) = a
    a * (√(x+a) - √x) - a = 0
    a * [ (√(x+a) - √x) - 1 ] = 0
    [ (√(x+a) - √x) - 1 ] = 0 OR a = 0
    (√(x+a) - √x) = 1 OR a = 0
    (√(x+a) - √x) = 1 OR (√(x+a) - √x) = (√(x+0) - √x) = (√x - √x) = 0

  • @xgx899
    @xgx899 3 месяца назад

    From (A-B)(A+B)=A^2-B^2, first expression times the second = a. Hence the second is 1. Another presentation by cybermath that is long-winded and trivial.